Joko Widodo and Xi Jinping's Anti Corruption Commonalities and Distinctiveness - Muhamad Iksan; Khairizah Fahrudin; Anggi Lestari (Journal Of Global Strategic Studies, 2025)
ABSTRACT Our paper attempts to describe two main questions: first, what anti-corruption strategy that both two President exercised their power and maintain legitimacy crucial for their presidency, Xi from 2012 up to present and Jokowi from 2014 to 2024. We are interested to discuss fuller on why did Xi and Jokowi took these strategies. Second, what are the outlook for the anti-corruption measures can be taken near the future, for Jokowi up to 2024 and for Xi will not have time limit post centralizing power under Xi’s power. We argue that Xi Jinping anti corruption targeted the political corruption related to his Chinese dreams confront with more certainty and stable domestic environment after he could centralized under his power. On the other hand, Jokowi first term has to overcome with a more dynamics domestic environment; although, in the beginnig of his presidency, he was perceived as anti-corruption politicians and acted adhere with good public governance principle, transparency and accountable. However, Jokowi’s second term altered his anti corruption stance. He governed his priority was no longer following transparency and accountable rather than economic development per se. This comparative study seeks to provide a deeper understanding of the relationship between anti-corruption strategies, power consolidation, and political legitimacy within presidential regimes that differ in their institutional characteristics. Keywords: Anti corruption, political corruption, comparative case of China and Indonesia ABSTRAK Artikel ini mengkaji dua pertanyaan utama: (1) bagaimana strategi antikorupsi yang dijalankan Xi Jinping (sejak 2012 hingga kini) dan Joko Widodo (2014–2024) digunakan sebagai instrumen untuk mempertahankan dan memperkuat legitimasi kekuasaan; serta (2) bagaimana prospek kebijakan antikorupsi pada periode kepemimpinan berikutnya, khususnya berakhirnya masa jabatan Jokowi pada 2024 dan rezim Xi yang tidak lagi terikat batasan masa jabatan setelah pemusatan kekuasaan di bawah otoritasnya. Kami berargumentasi bahwa strategi antikorupsi Xi berfokus pada pemberantasan korupsi politik yang mengancam konsolidasi kekuasaannya dan realisasi Chinese Dream, terutama dengan menciptakan lingkungan domestik yang dianggap lebih stabil dan terkendali. Sebaliknya, pemerintahan Jokowi pada periode pertama berupaya memperkuat legitimasi melalui citra antikorupsi dan penerapan prinsip tata kelola pemerintahan yang baik, transparansi, serta akuntabilitas. Namun, pada periode kedua, prioritas kebijakan Jokowi mengalami pergeseran menuju agenda pembangunan ekonomi, sehingga komitmen terhadap reformasi antikorupsi cenderung melemah. Kajian komparatif ini berupaya memberikan pemahaman yang lebih mendalam mengenai hubungan antara strategi antikorupsi, konsolidasi kekuasaan, dan legitimasi politik dalam rezim presidensial yang berkarakter berbeda secara institusional. Kata Kunci: antikorupsi, korupsi politik, legitimasi kekuasaan, studi komparatif, Cina, Indonesia